Clinical and Immunological Analysis of Cutaneous Leishmaniasis before and after Different Treatments - José A. O'Daly; Humberto M. Spinetti; Joe Gleason; María B. Rodríguez (Journal of Parasitology Research)
Amastigotes from L. (L.)amazonensis (La), L. (L.)venezuelensis (Lv), L. (V.)brasiliensis (Lb), and L. (L.)chagasi (Lch) were cultured in a free cells liquid culture medium. Patients (n=87) from a cutaneous leishmaniasis (CL) hyperendemic region receiving different treatments were followed up from January 1994 to August 2000. Time for remission of lesions were spontaneous remission (SR) 7 weeks; Glucantime (Glu) chemotherapy 9 weeks; immunotherapy with La, Lv, Lb, and Lch amastigotes Tosyl-Lysil Chloromethyl-ketone (TLCK) treated and Nonidet P-40(NP-40) extracted (VT) 7 weeks. Delayed type hypersensitivity (DTH) response with leishmanine intradermic reaction (IDR) was higher in CL patients than healthy controls (P<0.05) and increased in active secondary versus primary infection (P<0.001) with diagnostic value 1.74 for active infection and 1.81 postclinical remission. Antibodies to amastigotes characterized by Enzyme Linked Immunosorbent Assay (ELISA) decreased in sera postclinical remission versus active infections (P<0.001), with a diagnostic value from 1.50 to 1.84. Immunoblottings antigenic bands frequency as well as Integral Optical Density (IOD) Area Densitometry decreased with sera from SR, after Glu or VT treatments in CL volunteers. Intracellular parasitism is due to normal antibodies recognizing parasite antigens after inoculation by vector. VT vaccine induced mainly cellular immunity, for remission of lesions and protection from CL infection.